2008
DOI: 10.1149/1.2804763
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Electrodeposition of Magnesium in Ionic Liquids

Abstract: The electrochemical deposition of magnesium was investigated in the ionic liquids 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIm BF4 ), 1-butyl-1-methylpyrrolidinium triflate (BMP TfO), and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfo nyl)amide (BMP Tf2N ). The electrochemical window of the imidazolium ionic liquid was insufficient for reduction of magnesium triflate, whereas the BMP systems can be used for the reduction of several magnesium salts. Studies of the reduction of other magnesium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 12 publications
4
92
0
2
Order By: Relevance
“…One of the most serious issues is on the Mg negative electrode, i.e., the reversible Mg plating and stripping hardly realized in the various electrolyte solutions, because of the formation of insulating surface film. [2][3][4][5] Although the Grignard reagent based solutions can achieve the high reversible Mg plating and stripping reaction, 1,6,7 the solutions have critical disadvantages, such as low ionic conductivity, poor chemical and electrochemical stability. Recently, however, it was reported that the reversible Mg plating and stripping was achieved with Mg(N(CF 3 SO 2 ) 2 ) 2 (Mg(TFSA) 2 ) dissolved in triethyleneglycol dimethyl ether (triglyme) based solutions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most serious issues is on the Mg negative electrode, i.e., the reversible Mg plating and stripping hardly realized in the various electrolyte solutions, because of the formation of insulating surface film. [2][3][4][5] Although the Grignard reagent based solutions can achieve the high reversible Mg plating and stripping reaction, 1,6,7 the solutions have critical disadvantages, such as low ionic conductivity, poor chemical and electrochemical stability. Recently, however, it was reported that the reversible Mg plating and stripping was achieved with Mg(N(CF 3 SO 2 ) 2 ) 2 (Mg(TFSA) 2 ) dissolved in triethyleneglycol dimethyl ether (triglyme) based solutions.…”
Section: Introductionmentioning
confidence: 99%
“…We first reported the electrodeposition of magnesium in imidazolium-based and piperidine-based ionic liquids [26][27][28][29]. Cheek et al studied the electrodeposition of magnesium in imidazolium-based ILs and pyrrole-based ILs containing a Grignard reagent or several inorganic magnesium salts [30]. Recently, Morita et al [31,32] reported Mg electrodeposition from the electrolyte consisted of quaternary ammonium-based ILs with Grignard reagents or simple Mg salt, and they also synthesized a series of imidazolium-based ILs and examined the electrodeposition of magnesium from the solution mixed the ILs with a Grignard reagent [33].…”
Section: Introductionmentioning
confidence: 99%
“…ILs have been applied as "ionic solvents" of the electrolytes containing organo-magnesium complexes, and the resulting Mg-complex/IL systems can be worked as efficient electrolytes for reversible Mg deposition-dissolution. [32][33][34][35][36] As a result, higher efficiencies of Mg deposition-dissolution were achieved in those systems than that without IL. Recently, Bertasi et al reported Mg electrolytes based on 1-ethyl-3-methylimidazolium chloride (EMImCl) with AlCl 3 and amorphous δ-MgCl 2 exhibited highly reversible behavior.…”
mentioning
confidence: 97%